The Impact of ROA, BOPO, FDR, CAR, NPF on Mudharabah Profit Sharing Rate - Bramandita Bramandita; Harun Harun (Journal of Islamic Economic Laws, 2020)
This research was conducted to analyze the effect of Return on Assets (ROA), Operational Cost of Operating Income (BOPO), Financing Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), and Non-Performing Financing (NPF) on the level of profit-sharing at Mudharabah Banks Syariah with Case Study of BNI Syariah Bank in Indonesia. The data used is using the data recorded in the Financial Services Authority and financial reports published in 2016-2018. The data analysis method that will be used is Ordinary Least Square OLS after a series of Classical Assumptions tests. This research results that were partially finding the independent variables ROA, BOPO, FDR, and CAR have a significant effect. Meanwhile, the NPF variable does not have a significant effect on the Mudharabah Profit Sharing variable. This study shows that the NPF ratio is a picture of non-performing loans that do not significantly affect mudharabah profit-sharing, emphasizing the superiority of sharia contracts, especially mudharabah contracts.